ACTIVATING STUDENTSâ MULTIPLE INTELLIGENCES IN SPEAKING ACTIVITIES - Adityas, M Tolkhah (Universitas Ahmad Dahlan, 2016)
Language competence can be achieved by developing studentsâ intelligences. However, the fact that studentsâ potentials and intelligences vary has often been ignored. Appropriate learning activities are therefore needed to help students optimize such intelligences.Â This article aims at discussing how language teachers contribute to the enhancement of Multiple Intelligences in foreign language teaching, particularly in speaking classes. The paper also reviews the types of intelligences defined by Howard Gardner and proponents of this theory in terms of language teaching as well as exemplifies pedagogical methodologies by which studentsâ multiple inttelligence can be activated in speaking activities.Â